The Effect Of PER, PBV, And DER On Share Price Studies In The Energy Sector Listing On The IDX Period 2023 - Tamyis, M Hidayatul; Zaki, Achmad (SEAN Institute, 2024)
This study aims to obtain evidence regarding the effect of Price Earning Ratio (PER), Price Book Value (PBV) and Debt to Equity Ratio (DER) on stock prices. The population in this study amounted to 82 companies incorporated in the IDX energy sector stocks in 2023. This research uses quantitative methods consisting of classical assumption tests and multiple linear regression tests. The hypothesis in this study used the help of the SPSS 25 program. The results of this study indicate that PER has a sig value of 0.031 < 0.05 which means a significant negative effect, PBV has a sig value of 0.102 < 0.05 which means it has no significant effect on stock prices and DER has a sig value of 0.583 < 0.05 which means it has no significant effect on stock prices in the study of energy sectors listed on the IDX for the period 2023.